Determining the geographical position of a caller in GSM system / Syaidatul Naim Mohamad Nawawi - Mohamad Nawawi, Syaidatul Naim (2001)
The Mobile Station Location (MSL) technology is about determining the geographical position (latitude, longitude) of any wireless digital communications device, or Mobile Station (MS). Basically, the project focuses on the development of MSL system which can locate a mobile station in GSM system by using a Triangulation Solution method. The Mobile Radio Analyzer (MA10) is used to see and measure the activities involved between a mobile station and a serving Base Transceiver Station (BTS). Visual Basic (VB) program has been used in simulation of data obtained from MA10. The accuracy of geographical positioning of MS depends largely on the number of BTS in a given area. Ms in an urban area can be more accurately located compared with rural area.